2002
DOI: 10.1530/eje.0.1460751
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of Graves' ophthalmopathy on health-related quality of life

Abstract: Objective: Little is known about the long-term effects of Graves' ophthalmopathy (GO) on healthrelated quality of life (HRQL) after the eye treatment is considered to be finished. The aim of this study was to quantify these effects using validated HRQL questionnaires. Design: A cross-sectional follow-up study was carried out in GO patients who had started radiotherapy and/or prednisone treatment between 1982 and 1992. Methods: Between 1998 and 2000 these patients received an HRQL questionnaire containing the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
2
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 14 publications
6
72
2
7
Order By: Relevance
“…As a result, our findings may not be fully comparable with those of other studies. However, the lack of a questionnaire that assesses the psychological status, as well as the general, clinical and psychosocial aspects of GD in all its complexity, as well as the response to medical and/or surgical treatment, is acknowledged in the international literature [2,18,28]. Surprisingly, our results showed that none of the patient characteristics were significantly associated with a higher HRQOL impairment after surgery.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…As a result, our findings may not be fully comparable with those of other studies. However, the lack of a questionnaire that assesses the psychological status, as well as the general, clinical and psychosocial aspects of GD in all its complexity, as well as the response to medical and/or surgical treatment, is acknowledged in the international literature [2,18,28]. Surprisingly, our results showed that none of the patient characteristics were significantly associated with a higher HRQOL impairment after surgery.…”
Section: Discussioncontrasting
confidence: 57%
“…Based on the most frequently observed symptoms and questionnaires found in the international literature (Medical Outcomes Study-24 questionnaire [13]; Short Form-36 questionnaire [14]; EuroQol VAS Questionnaire [15]; National Eye Institute Visual Function Questionnaire [16]; Profile of Mood States [17]; Graves' ophthalmopathy Quality of Life Questionnaire-GOQOL [18]), we developed a questionnaire to measure the HRQOL in patients who had undergone total thyroidectomy for GD. Many of the questions included in our questionnaire were derived from these previously cited studies and were thus considered to be validated.…”
Section: Questionnairementioning
confidence: 99%
“…TED has the potential to cause facial disfigurement and/or visual deficits, impacting on employment, hobbies and self-confidence, and frequently leading to a withdrawal from social interactions. Several previous studies have demonstrated a marked reduction in the quality of life of patients with TED as compared to the general population and patients with other chronic diseases (3)(4)(5)(6), to a degree that is often underappreciated by healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Vários grupos relataram alterações na qualidade de vida dos pacientes com OG tanto nos aspectos físicos como emocionais (3,23) . Sintomas como depressão, ansiedade e estresse relacionados a atividades sociais e de trabalho estão presentes em grande parte dos indivíduos, embora a OG esteja às vezes camuflada em formas de apresentação que podem não parecer graves ao médico (2,24) .…”
unclassified
“…Escores menores que três significam oftalmopatia em fase não inflamatória (Tabela 1). Para avaliar as alterações oculares da doença de Graves utilizou-se a classificação "NOSPECS", que permitiu distribuir os pacientes portadores de OG em três categorias: leve ("NOSPECS" 2a, 30-a, 40-a), moderada/grave ("NOSPECS" 2b, 3bc, 4bc) e grave ("NOSPECS" 5bc, 6a-c) (Tabela 2) (21,23) .…”
unclassified